Influence of gamma irradiation on the isolation of bioactive 4-hydroxyisoluceine compound from fenugreek and its enhanced antifungal properties. (April 2022) - Gajbar, Tanzeembanu D.; Satapute, Praveen; Jogaiah, Sudisha
Abstract: In the current study, the influence of gamma radiation for the enhanced activity of 4-hydroxyisoluceine (4-HIL) that posses an in vitro inhibition of blast pathogen, thereby protecting rice plants was thoroughly investigated. It was found that methanolic crude extract of 20 Gy gamma irradiated extract provided remarkable saponin content (7.15 g 100 g −1 ) compared to non-irradiated extracts. When irradiated and non-irradiated crude extracts on separation by thin layer chromatography (TLC) showed an Rf value of 0.61 that matched with the Rf value of the standard 4-HIL compound. Further, the TLC partial purified compound (10 μl) upon ejected to high performance liquid chromatography (HPLC) produced a single peak at a retention time of 5.1 min. Moreover, a fair to good anti-blast properties was noticed in all the concentrations of the purified 4-HIL compound. Analyses of anti-blast compound using liquid chromatography-mass (LCMS) spectrometry and 2-D nuclear magnetic resonance spectroscopy (NMR) detected the presence of 4-HIL at m/z value of 146 and CD3 OD resonating at 3.86 ppm respectively. Lastly, under greenhouse conditions, primed plants with 4-HIL compound at 150 μg mL −1 showed a significant disease protection of 77% over the control plants. Overall, this study witnessed an enhanced anti-blast secondary compound from fenugreek seeds irradiated with gamma rays which can be used as safe agrochemicals for plant protection, particularly for rice production. Highlights: Enhanced bioactive compound in fenugreek extract is influenced by gamma radiation. The γ irradiated methanolic extract (20 Gy) recorded high saponin content. A bioactive compound, 4-hydroxyisoluceine (4-HIL) was isolated from irradiated extract. A remarkable In vitro anti-blast activity was observed in the isolated 4-HIL compound. Primed plants with 4-HIL compound provided significant protection against blast disease.